Age, memory loss and perceptions of dementia in South Asian ethnic minorities. (1st February 2019) - Giebel, Clarissa M.; Worden, Angela; Challis, David; Jolley, David; Bhui, Kamaldeep Singh; Lambat, Ahmed; Kampanellou, Eleni; Purandare, Nitin
ABSTRACT: Background: South Asian older adults are represented less frequently in mainstream mental health services or those for people with dementia. This study aimed to explore in detail the perceptions of dementia (symptoms, causes, consequences, treatments) held by South Asians and to discern how these understandings vary by age and by the self-recognition of memory problems, as these influence help-seeking behaviour. Methods: Participants were allocated to three groups: younger adults; older adults; and older adults with subjective memory problems. They completed the semi-structured Barts Explanatory Model Inventory for Dementia schedule, whilst older adults also completed measures of cognition (MMSE), and depression (GDS). Interviews were conducted in English, Gujarati or Urdu. Results: Groups were similar in identifying unusual forgetting and confusion as the most frequent symptoms; stress and age as the most frequent causes; and talking to your GP/nurse, taking medication, and talking to family and friends as the most frequent treatments. Younger adults more often knew about risk factors and reported practical consequences more than older adults. Older adults with subjective memory problems were more likely to describe sleep related problems or symptoms commonly associated with depression. They more often cited as causes of dementia lack of sleep, side effects of medication and medical reasons, and mentioned religion as a means to cope. Conclusions: Findings highlight variability in perceptions of dementia across the South Asian Community and identify specific areas where dementia awareness could be raised in South Asian sub-groups to improve timely diagnosis, treatment outcomes and service access.